2005
DOI: 10.1007/s00534-005-0985-0
|View full text |Cite
|
Sign up to set email alerts
|

An extramural gastrointestinal stromal tumor of the duodenum mimicking a pancreatic head tumor

Abstract: We report the case of a 53-year-old woman with a gastrointestinal stromal tumor (GIST) of the duodenum that showed only extramural growth, mimicking a pancreatic tumor. Preoperatively, computed tomography (CT) and angiography revealed a hypervascular mass, 3.0 cm in diameter, in the pancreatic head. Hypotonic duodenography showed compression of the second and third portions of the duodenum by the pancreatic lesion. Endoscopic examination showed no specific mucosal abnormalities in the duodenal lumen. The pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
25

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 7 publications
0
27
0
25
Order By: Relevance
“…5,6 These tumors may also occur in the peritoneum and extragastrointestinal sites. 9 The small intestine is the second most common site of GISTs, of which approximately 20% are found in the duodenum. 8 Duodenal GISTs are uncommon tumors, representing only nine of the 101 tumors (9%) in this series.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 These tumors may also occur in the peritoneum and extragastrointestinal sites. 9 The small intestine is the second most common site of GISTs, of which approximately 20% are found in the duodenum. 8 Duodenal GISTs are uncommon tumors, representing only nine of the 101 tumors (9%) in this series.…”
Section: Discussionmentioning
confidence: 99%
“…The GISTs in the case reports were both also suspected to be neuroendocrine tumors and were treated by a pylorus-preserving pancreaticoduodenectomy and a segmental resection of the duodenum and duodenojejunostomy and pancreatic head resection with duodenal segmentectomie respectively. In the case series by Sandrasegaran et al, the preoperative CT scans of 19 patients with a duodenal GIST were reviewed [7]. They found that 2 of the 19 scans were reported as possible pancreatic head cancers.…”
Section: Discussionmentioning
confidence: 98%
“…The tumors are frequently located in close relationship to the ampulla of Vater, this determining surgical treatment strategy. An extensive search of the English literature found only for previous case reports [3,6,7,14] and one case series [8] describing duodenal GISTs presenting as a pancreatic head cancers. The GISTs in the case reports were both also suspected to be neuroendocrine tumors and were treated by a pylorus-preserving pancreaticoduodenectomy and a segmental resection of the duodenum and duodenojejunostomy and pancreatic head resection with duodenal segmentectomie respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, preoperative imaging studies showed that the mass lesion originated from the head of pancreas, and gastroduodenoscopy showed that the duodenum mucosa was normal. Therefore, this tumor was considered to be a primary pancreatic head tumor with an exophytic growing pattern (5,6,10). The most important prognostic factors for GISTs are the tumor size and mitotic count.…”
Section: Case Presentationmentioning
confidence: 99%
“…These tumors may originate from any location in the entire gastrointestinal tract, and the most susceptible sites are the stomach (40%-60%), small intestine (30%-40%), colon and rectum (5%), and esophagus (5%), whereas only 3%-5% of GISTs occur in the duodenum (4)(5)(6). There are also sporadic reports of GISTs that arise from the peritoneum, omentum, mesentery, and retroperitoneum (2,3,7).…”
Section: Introductionmentioning
confidence: 99%